Assessment of cold tolerance at early developmental stages and allelic variation at candidate genes in South American rice germplasm - Pachecoy, Maria Ines; Ramirez, Ignacio Abel; Marín, Alfredo; Pontaroli, Ana Clara (Springer, 2018)
Rice is susceptible to cold during early developmental stages. Most tolerant cultivars have been developed for other conditions than those occurring in South America’s rice growing areas, or their grain type is not suitable for the local markets. If locally adapted varieties were available, growers could anticipate sowing date, making flowering time coincide with the moment of maximum solar radiation and increasing yields. In this work, 116 rice inbred lines and varieties of diverse origin within the South American gene pool were tested for seedling survival and germination percentage under low temperature in controlled conditions. As a result, lines used as controls responded as expected, whereas lines with similar behavior to controls, intermediate between susceptible and tolerant controls and more extreme than controls were detected at both seedling and germination stages. Allelic variation at candidate genes OsGSTZ1, OsGSTZ2 and OsCDPK13 was analyzed in a subset of ten contrasting lines. Ten out of thirty-four polymorphisms detected in all three genes were associated with cold tolerance in these lines. A functional marker, designed from an aminoacid-changing SNP found in gene OsGSTZ2, was tested in the 116 lines. As a result, a tight association was observed between cold tolerance and marker score. In conclusion, wide variability for cold tolerance at early developmental stages has been detected in rice advanced breeding materials that are adapted to local growing conditions. Also, a functional marker tightly associated with the trait is available for performing marker assisted selection